Practical sense, rationality and teacher education: the role of practice in the curricula of Physical Education teacher education programs at public institutions in the State of São Paulo (Agora for Physical Education and Sport, 2025)
The study analyzed the role of practical components in Physical Education teacher training curricula in Brazil through interviews with seven educators from public institutions in São Paulo. Results were categorized as: i) allocation of space, reserved schedule slots, and relative independence of practice; and ii) application of knowledge, influenced by academicization. Criticisms highlight the marginalization of practical components, revealing gaps and imbalance in curricular structuring. These issues are tied to the hegemonic paradigm shaping curricula and related policies. The findings underscore the need for greater integration and balance to address the marginal status of practical components in education.
Keywords: Teacher education; pedagogical process; educational policy; school Physical Education; curricula